2021
DOI: 10.1371/journal.pone.0247253
|View full text |Cite
|
Sign up to set email alerts
|

Convergent antibody evolution and clonotype expansion following influenza virus vaccination

Abstract: Recent advances in high-throughput single cell sequencing have opened up new avenues into the investigation of B cell receptor (BCR) repertoires. In this study, PBMCs were collected from 17 human participants vaccinated with the split-inactivated influenza virus vaccine during the 2016–2017 influenza season. A combination of Immune Repertoire Capture (IRCTM) technology and IgG sequencing was performed on ~7,800 plasmablast (PB) cells and preferential IgG heavy-light chain pairings were investigated. In some pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…Our work supports the following model, generalizing observed constraints on gene usage by some antibodies 28,10,12,1424 . In nature, many heavy chain configurations yield effective binding of a given antibody target.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our work supports the following model, generalizing observed constraints on gene usage by some antibodies 28,10,12,1424 . In nature, many heavy chain configurations yield effective binding of a given antibody target.…”
Section: Discussionsupporting
confidence: 86%
“…A clonotype can therefore be treated as the minimal functional group of antibodies. Next, as has been observed, nature repeats itself by creating similar clonotypes that appear to have the same function 2-21 , and these might be combined into groups. Such recurrences have been observed between donors, but also occur within single donors, as we will demonstrate.…”
Section: A Novel Approach To Grouping Antibodies Reveals Light Chain ...mentioning
confidence: 91%
See 1 more Smart Citation
“…'Public' response antibodies. 'Public' antibodies, those that are raised independently across multiple individuals against an immunodominant epitope, are of high interest to several fields of research, from vaccinology to drug discovery [70][71][72].…”
Section: (Sc57)mentioning
confidence: 99%
“…'Public' Response Antibodies. 'Public' antibodies, those that are raised independently across multiple individuals against an immunodominant epitope, are of high interest to several fields of research, from vaccinology to drug discovery (67)(68)(69). Several studies have already identified public SARS-CoV-2 response antibodies based on convergence towards particular clonotype lineages (12)(13)(14)(15)(16)(17)(18), but none have yet considered the fact that antibodies from different lineages can exert similar functions.…”
Section: Structural Clusters Frequently Span Multiple Clonal Lineagesmentioning
confidence: 99%